Modeling Epithelial Homeostasis and Perturbation in Three-Dimensional Human Esophageal Organoids - Masataka Shimonosono; Masaki Morimoto; Wataru Hirose; Yasuto Tomita; Norihiro Matsuura; Samuel Flashner; Mesra S. Ebadi; Emilea H. Okayasu; Christian Y. Lee; William R. Britton; Cecilia Martin; Beverly R. Wuertz; et al. (Biomolecules)
Background: Esophageal organoids from a variety of pathologies including cancer are grown in Advanced Dulbecco’s Modified Eagle Medium-Nutrient Mixture F12 (hereafter ADF). However, the currently available ADF-based formulations are suboptimal for normal human esophageal organoids, limiting the ability to compare normal esophageal organoids with those representing a given disease state. Methods: We have utilized immortalized normal human esophageal epithelial cell (keratinocyte) lines EPC1 and EPC2 and endoscopic normal esophageal biopsies to generate three-dimensional (3D) organoids. To optimize the ADF-based medium, we evaluated the requirement of exogenous epidermal growth factor (EGF) and inhibition of transforming growth factor-(TGF)-β receptor-mediated signaling, both key regulators of the proliferation of human esophageal keratinocytes. We have modeled human esophageal epithelial pathology by stimulating esophageal 3D organoids with interleukin (IL)-13, an inflammatory cytokine, or UAB30, a novel pharmacological activator of retinoic acid signaling. Results: The formation of normal human esophageal 3D organoids was limited by excessive EGF and intrinsic TGFβ-receptor-mediated signaling. Optimized HOME0 improved normal human esophageal organoid formation. In the HOME0-grown organoids, IL-13 and UAB30 induced epithelial changes reminiscent of basal cell hyperplasia, a common histopathologic feature in broad esophageal disease conditions including eosinophilic esophagitis. Conclusions: HOME0 allows modeling of the homeostatic differentiation gradient and perturbation of the human esophageal epithelium while permitting a comparison of organoids from mice and other organs grown in ADF-based media.